A general procedure for extraction of bias dependent dynamic self heating model parameters - Andersson, K.; Fager, C.; Pedro, J.C. (IEEE MTT-S International Microwave Symposium Digest, 2005, 2005)
A general method for characterizing electrothermal interaction due to self heating is proposed. The characterization is performed using only electrical measurements and is directly applicable to a wide range of device technologies. A rigorous small-signal analysis of the electrothermal problem forms the basis for the characterization and model parameter extraction technique. The proposed technique allows for extraction of both the thermal impedance and the thermal coefficient. The small-signal analysis is valid for any N-port subject to self-heating from a single heat source. The method is demonstrated on a 200 μm pHEMT device